Distribution status and ethnomedicinal importance of genus Rosa L. (Rosaceae) in India - Singh, Kanwaljeet; Sharma, Yash Pal; Gairola, Sumeet (Ethnobotany Research and Applications, 2023)
Background: The knowledge of geographical distribution and ethnobotanical uses is critical for the effective conservation and utilization of native plant genetic resources. No attempt has been made to amalgamate and analyze all of the available information on the ethnobotany, and distribution of Rosa in India. Therefore, this work aimed to provide a comprehensive review on the geographical distribution, and ethnobotany of the genus Rosa, as well as to give insights into possible future research opportunities. Methods: Information on geographical distributions was compiled using regional floras, books, eFloras, regional herbaria, research articles related to distribution, and ethnobotanical studies of Rosa in India and online databases were also searched for the distribution records at global level. Results: The data revealed a total of 38 species of roses in India with 26 wild, 10 cultivated and 2 wild as well as cultivated species. The highest number of Rosa species were found in Jammu and Kashmir (20 taxa), followed by Himachal Pradesh (17 taxa), Uttar Pradesh (11 taxa), Ladakh and Assam (9 taxa each), Uttarakhand, and West Bengal (8 taxa each), Tamil Nadu (5), Karnataka, Meghalaya, Sikkim (4 taxa each), Delhi, Manipur, and Odisha (3 taxa each), Arunachal Pradesh, Bihar, Kerala, and Punjab (2 taxa each), Andhra Pradesh, Haryana, Madhya Pradesh, Maharashtra and Rajasthan (1 taxon each). Rosa webbiana, R. moschata, R. macrophylla and R. sericea were the most widely distributed in the Western Himalayan region. Besides, ten species were used to treat several health ailments including cough, eye infection, skin ailments, epilepsy, respiratory trouble, jaundice, inflammation, and leucorrhea, hepatitis, sexual dysfunction, fever, flu, diarrhea, stomachache, cancer. These wide spectrum ethnobotanical applications of the genus reflect their long association with prevailing ethnic communities across regions. Conclusion: The species of Rosa have economic as well as medicinal value. Therefore, future research is required on phytochemical, pharmacological and toxicological aspects of the less investigated species of Rosa to explore their economic and medicinal potential from India. Keywords: Rosa species, Ethnobotany, Ecogeographical distribution, India